2022
DOI: 10.18775/ijied.1849-7551-7020.2015.82.2001
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Commodity Export and Nigeria’s Gross Domestic Product Between 2009 to 2018

Abstract: Agricultural exports have undoubtedly played a crucial role in boosting Nigerian economic growth and other sub-Saharan countries. It has been contributing to foreign-exchange earnings in Nigeria and is used to promote other capital projects. Agriculture has been the main contributor to the Nigerian external sector before the discovery of oil. This study evaluates the linkage between selected agricultural commodity export and Nigeria’s Gross Domestic Product (GDP) between 2009 and 2018. The work is quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Agriculture emphatically contributed to the Nigerian economy during the pre-colonial, colonial, and post-colonial era. However, its contribution to the growth of the nation's Gross Domestic Product (GDP) has been dwindling in recent times due to over-dependence of successive administrations on oil since its discovery [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agriculture emphatically contributed to the Nigerian economy during the pre-colonial, colonial, and post-colonial era. However, its contribution to the growth of the nation's Gross Domestic Product (GDP) has been dwindling in recent times due to over-dependence of successive administrations on oil since its discovery [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, they found that export agricultural price index on products such as live animals, animal products and vegetable product does not significantly impact on economic growth in Nigeria, hence, they recommended that government should invest more on areas such as live animals, animal products and vegetable products so that they will impact positively on economic growth in the near future thereby strengthen the diversification agenda of the Government of Nigeria. Victor and Onyeukwu (2022) evaluated the linkage between selected agricultural commodity export and Nigeria's gross domestic products (GDP) between 2009 and 2018. The research was a quantitative work that adopted a descriptive research design where data on sesame seed export, cashew export, cocoa beans export, exchange rate, Gross fixed capital formation, real gross domestic product and agricultural commodity export were sourced from the Central Bank of Nigeria Statistical Bulletin and the United Nation's Commercial Trade Statistics, the ordinary least squares regression analysis and the Granger Causality test were employed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These include honey, processed milk, meat from snails, animal skins, and dry-cured meat (Kilishi) [3]. Meat is categorized as one of the six major agricultural commodities in Nigeria [4] and processed meat could be classified as ham and bacon, sausages, cold and roast meat [5]. Nigeria meat exports were at the level of 52 thousand US dollars in 2018, down from 236 thousand US dollars the previous year which was a change of 77.97% possibly due to safety concerns [6].…”
Section: Introductionmentioning
confidence: 99%